“My Decision: A Memoir” and “The Young Widow Memoir: Grief and the Rebuilding of Fractured Identity” - Den Elzen, Katrin (Curtin University, 2018)
This creative writing doctorate consists of two components: firstly a creative work, namely a grief memoir, which depicts the illness and death of my husband and my subsequent recovery and rebuilding of fractured identity. Secondly the exegesis, which examines the representation of grief and the reconstruction of narrative identity in memoirs depicting young widowhood. It positions the theoretical approach at the intersection of autobiography scholarship and narrative psychology, specifically the Dialogical Self Theory.